2013
DOI: 10.1186/1471-2164-14-640
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics reveals distinct host-interacting traits of three major human-associated propionibacteria

Abstract: BackgroundPropionibacteria are part of the human microbiota. Many studies have addressed the predominant colonizer of sebaceous follicles of the skin, Propionibacterium acnes, and investigated its association with the skin disorder acne vulgaris, and lately with prostate cancer. Much less is known about two other propionibacterial species frequently found on human tissue sites, Propionibacterium granulosum and Propionibacterium avidum. Here we analyzed two and three genomes of P. granulosum and P. avidum, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 51 publications
(79 reference statements)
5
42
0
Order By: Relevance
“…In this study, we extracted surface proteins from washed bacterial pellets by lithium stripping. Our results are consistent with the CAMP factor 1 protein being associated with the surface but not firmly bound to it, as it can be removed from whole bacteria by trypsin cleavage [46]. Previous studies have reported the presence of P .…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we extracted surface proteins from washed bacterial pellets by lithium stripping. Our results are consistent with the CAMP factor 1 protein being associated with the surface but not firmly bound to it, as it can be removed from whole bacteria by trypsin cleavage [46]. Previous studies have reported the presence of P .…”
Section: Discussionsupporting
confidence: 91%
“…After removal of human DNA sequences and low-quality reads, we obtained an average of 1.08 gigabase pairs (Gbp) per sample (6.9 × 10 7  bp – 4.8 × 10 9  bp), sufficient to cover the microbial diversity of skin samples24. We mapped the cleaned sequencing reads to our reference genome set, which consists of 1,252 bacterial and 272 fungal genomes from the HMP reference genome database and several additional genomes of skin microorganisms: Propionibacterium avidum 2526 , Propionibacterium granulosum 26 , Propionibacterium humerusii 27, and P. acnes bacteriophage2829. To cover different P. acnes strains, we also included the P. acnes pan-genome in the reference19.…”
Section: Resultsmentioning
confidence: 99%
“…Limited genomic information exists for P. granulosum . Previous comparative analysis based on two draft genomes revealed that, compared to P. acnes, P. granulosum lacks virulence-related factors such as CAMP factors and sialidases, and exhibits no neuraminidase and hyaluronidase activities26. The bacterium may provide protection to the skin with less production of virulence-associated elements.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown an abundance of CAMP1 as surface-exposed factor [19], [30], [31]. In contrast to other CAMP factors, such as CAMP2 and CAMP4, the gene encoding CAMP1 is not located on an island-like genomic region [32]. It is possible that differences in the SLST target region are important for the transcription of CAMP1 resulting in clade-specific differences.…”
Section: Discussionmentioning
confidence: 99%